Pertumbuhan Bibit Kamboja Putih (Plumeria Alba L.) Asal Setek Beda Ukuran Panjang yang Diberi Zat Pengatur Tumbuh - Iga Azalia Lamonda; Adiwirman Adiwirman; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
White frangipani plant is an ornamental plant that is currently being much developed. The main problem in the development of white frangipani is sexual reproduction has a weakness, some of them take a long time, and genetic differences with the parent. So, the vegetative propagation as the alternative. One way of vegetative propagation by cuttings can be done, and the length of the cuttings was will be the success of the cuttings, but the success is relatively low due to the inhibition of root formation. So, added of growth regulators is one alternative make to form roots properly. This study aims to increase the success of white frangipani plant propagation through cuttings. The research was carried out in the experimental garden of the Faculty of Agriculture, Riau University, Bina Widya Campus Km 12.5 Pekanbaru from September to December 2021. The study was conducted in the form of a 3 x 4 factorial trial with a completely randomized design with 3 replications. The first factor, the length of the cuttings were: 10 cm, 15 cm, and 20 cm, and the second factor was the PGR concentration which consisted of: without PGR, 100 ppm, 150 ppm, and 200 ppm. The results showed that the success of white frangipani plant propagation was only seen in the increase in shoot length and leaf length as the effect of the interaction between cutting length and ZPT concentration. The use of cuttings with a size of 20 cm resulted in longer shoots of 0.57 cm and 0.60 cm compared to 100 ppm and 150 ppm ZPT immersion when the cuttings were immersed in 200 ppm PGR concentration. The use of cuttings with a size of 20 cm resulted in 2.10 cm and 2.00 cm longer leaves compared to 100 ppm and 150 ppm ZPT immersion when the cuttings were immersed in 200 ppm PGRconcentration. Keywords:White Frangipani, Cutting Length Size, Concentrationof Growth Regulator